Sweet chestnut (Castanea sativa Mill.) bioclimatic suitability in Central Italy: future potential scenarios under climate change - Giorgia Di Domenico; Sergio Noce; Francesco Carbone; Giovanni D'Amico; Walter Mattioli (Annals of Silvicultural Research)
The ecological and economic relevance of sweet chestnut (Castanea sativa Mill.) has long been related to its wide geographical distribution and multipurpose products potential. In Central Italy and especially in Latium, sweet chestnut finds optimal environmental conditions for growth, supported by the application of traditional silvicultural practices. Thus, its distribution has been radically modified and controlled by man in order to manage it in profitable and diversified ways (e.g., by coppices or orchards) to produce a wide range of ecosystem services, marketable (wood, fruits) and not marketable (landscape, water regulation, etc.) products. Over the years, due to climate change, some productivity changes have been observed and new challenges are expected to manage and cultivate this species. Based on this background, this work aims at investigating the possible impacts of climate change on sweet chestnut in Central Italy in medium (2041-2060) and long term (2081-2100). Adopting a standard protocol for reporting species distribution model (ODMAP - Overview, Data, Model, Assessment, Prediction), four Earth System Models have been combined into two Shared Socio-economic Paths and two Time Horizons, to produce potential chestnut bioclimatic suitability maps. The outlined scenarios represent valuable information for future chestnut policy and management for defining specific strategies, considering the adaptive capacity of the species in terms of resilience from pathogenic attacks and response to innovative silvicultural treatments.